A study of methane production and growth of lai sindhi cattle fed cassava pulp and elephant grass supplemented by coconut meal : - Nguyen, Thanh Duy (Can Tho University, 2017)
The objectives of thesis was to study the use ofcassavava pulp as residuces replaced elephant grass in diet and coconut meal as source of by-pass protein for growth of Lai Sindhi